Geometry Investigation and Performance Optimization of a Single-Mass Piezoelectric 6-DOF IMU - Almabrouk, H.; Mezghani, B.; Agnus, G.; Kaziz, S.; Bernard, Y.; Tounsi, F. (Engineering, Technology & Applied Science Research, 2020)
This paper explores the fundamental steps towards the development of a 6-axis piezoelectric Inertial Measurement Unit (IMU). The main specification of the reported device is its ability to concurrently detect 3-axis acceleration and angular velocity using a single mass-based design. This work represents a detailed numerical analysis based on a finite element model. Experimental reported data are exploited to validate the FEM model in terms of acceleration detection which is ensured through the direct piezoelectric effect. The angular rate is detected thanks to the Coriolis effect by ensuring drive and sense modes. Using a Finite Element Analysis (FEA), light was shed on the different basic parameters that influence the sensor performance in order to present an optimized design. A detailed geometrical investigation of factors such as anchor position, optimized locations for sensing electrodes, proof-mass dimensions, PZT thickness, and operating frequency is illustrated. The 6-DOF sensor outputs are extracted in terms of the original and the optimized design. The amelioration rate of sensitivity is found to be up to 165% for linear acceleration, while for angular rate sensing, the lateral sensitivity is ameliorated by about 330% and is multiplied by around ten times in the normal axis. The optimized design exhibits a good acceleration sensitivity of 260mV/g in the lateral axis and 60.7mV/g in the z-axis. For angular rate sensing, the new design is more sensitive along the longitudinal axis than the lateral one. Sensitivity values are found to be 2.65µV/rad/s for both x-and y-axis, and 1.24V/rad/s for the z-axis.